ChemInform Abstract: Octa‐1, 7‐diene‐4, 5‐diamine Derivatives: Useful Intermediates for the Stereoselective Synthesis of Nitrogen Heterocycles and Ligands for Asymmetric Catalysis. Issue 35 (August 2016) - Gualandi, Andrea; Grilli, Stefano; Savoia, Diego
Abstract: Review: [65 refs.